2009
DOI: 10.1109/tdmr.2009.2022631
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Migration on Electronic Chip Resistors in Chloride Environments

Abstract: Abstract-Electrochemical migration behavior of end terminals on ceramic chip resistors (CCRs) was studied using a novel experimental setup in varying sodium chloride concentrations from 0 to 1000 ppm. The chip resistor used for the investigation was 10-kΩ CCR size 0805 with end terminals made of 97Sn3Pb alloy. Anodic polarization behavior of the electrode materials was investigated using a microelectrochemical setup. Material makeup of the chip resistor was investigated using scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 16 publications
2
63
0
Order By: Relevance
“…For comparison, the resistance of the dendrites formed for Sn-Pb and lead free solder alloys under distilled water varies in the range of kOhms [3]. Similar resistance values were reported in the study of ECM on electronic chip resistors in chloride environments [6]. An increase of dendrite current with increase of duty cycle observed for 15.6 lg cm -2 of NaCl indicated that the longer ON cycles is more dynamically favourable condition for dendrite growth and suggests different morphology of dendrites formed under pulsed voltage.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…For comparison, the resistance of the dendrites formed for Sn-Pb and lead free solder alloys under distilled water varies in the range of kOhms [3]. Similar resistance values were reported in the study of ECM on electronic chip resistors in chloride environments [6]. An increase of dendrite current with increase of duty cycle observed for 15.6 lg cm -2 of NaCl indicated that the longer ON cycles is more dynamically favourable condition for dendrite growth and suggests different morphology of dendrites formed under pulsed voltage.…”
Section: Discussionsupporting
confidence: 73%
“…However, the process of ECM can be also influenced by the ionic contamination dissolved in the water layer [5][6][7], pH level, bias voltage [3,8], and the distance between the electrodes [9,10]. The conductivity of the water layer adsorbed on a PCBA is determined by the ionic contamination present on the surface as it affects the ion transport between the anode and cathode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al 53 studied the ECM of Sn under 100 mm-thick electrolyte layer containing 1 mM Cl À with a bias voltage of 3 V. They found that the initiation stage took about 100 seconds while the total ECM time (from the beginning of ECM test to the time when a short circuit occurs) was 119 seconds. Minzari et al 45 reported a similar phenomenon during the ECM of Sn-37Pb solder alloy in 10 ppm NaCl solution at a bias voltage of 3 V.…”
Section: 109mentioning
confidence: 68%
“…It is based on the observation that in impedance graphs ( Fig. 3), along the humidification curve, a dry region is followed first by a deliquescent region (sharp decrease in impedance), and then by a hygroscopic growth region (due to continuous condensation of water); the reverse happens during dehumidification when evaporation took place, followed by crystallization (sharp increase in impedance), which in turn led once again to a dry state.The ECM is typically studied by applying constant voltage and measuring the LC between interdigitated electrodes [29]. Under these conditions, the "BioLogic VSP" potentiostat was used to measure the low current passing through a conductive layer at 5 V DC and as a function of RH (30.0-90.0% RH).…”
Section: Impedance and Leakage Current Measurementsmentioning
confidence: 99%